PREVALENCIA DE BRUCELOSIS CAPRINA EN LA PROVINCIA DE BARRANCA, LIMA - Garro A., Edwin (2005)
The objetive of this study was to determine the prevalence of brucelosis in goats at the province of Barranca, Lima (districts of Paramonga, Pativilca, Barranca and Supe). The Rose Bengal agglutination test was used in 392 female goats older than 3 months that were not vaccinated against brucellosis. No positive samples were found posibly due to the effective programme of control and eradication carried out since 1997 by the Ministry of Health and SENASA (Servicio Nacional de Sanidad Agraria).